Effect of Th17 and Treg Axis Disorder on Outcomes of Pulmonary Arterial Hypertension in Connective Tissue Diseases - Gaowa, Saren; Zhou, Wenyong; Yu, Lilei; Zhou, Xiaohui; Liao, Kai; Yang, Kang; Lu, Zhibin; Jiang, Hong; Chen, Xiaofeng (Mediators of Inflammation, 2014)
This prospective cohort study is to verify the hypothesis that the balance of Th17 and Treg cells frequencies in the peripheral circulation is disturbed in patients with varying degrees of connective tissue diseases-associated pulmonary arterial hypertension (CTD-aPAH) and to prove the influence of Th17/Treg imbalance on prognosis. We detected the frequencies and absolute counts of Th17 and Treg cells and related serum cytokines secretion and expressions of key transcription factors in 117 patients with connective tissue diseases (CTD), 53 patients with CTD-aPAH, and 48 healthy volunteers. Moreover, the median value according to levels of Th17/Treg ratios in patients with CTD-aPAH was chosen as basis of group division for survival analysis. CTD-aPAH patients revealed significant increase in peripheral Th17 cells, Th17-related cytokines, and ROR γt mRNA levels. They also presented a significant decrease in Treg cells, Treg-related cytokines, and Foxp3 mRNA levels as compared with CTD patients and healthy controls. More importantly, the Th17/Treg ratio was significantly related to the severity and prognosis of CTD-aPAH. This study indicated that the Th17/Treg axis disorder plays a critical role in CTD-aPAH. Furthermore, the dynamic balance between Th17 and Treg cells was likely to influence prognosis of patients with CTD-aPAH.